FTIR and 1H-NMR studies of chiral (S)-(-)-2-methylbutyl 4′-(4″-hexyloxy-, (S)-(-)-2-methylbutyl 4′-(4″-(d13)-hexyloxy‒, (S)-(-)-2-methylbutyl 4′-(4″-octyloxy- and (S)-(-)-2-methylbutyl 4′-(4″-(d17)-octyloxyphenyl)benzoates. Issue 3 (2000) - Yeap Yeap, Guan-Yeow Guan-Yeow; Takanishi Takanishi, Yoichi Yoichi; Takezoe Takezoe, Hideo Hideo
Abstract : Four organic chiral compounds (S)-(-)-2-methylbutyl 4′-(4″-hexyloxy-, (S)-(-)-2-methylbutyl 4′-(4″-(d13 )- hexyloxy-, (S)-(-)-2-methylbutyl 4′-(4″-octyloxy- and (S)-(-)-2-methylbutyl 4′-(4″-(d17 )-octyloxy-phenyl)benzoates were synthesized via generalized methods and characterized by elemental analysis, FTIR and 1 H NMR. A noticeable difference between the compounds which possess hydrogenated achiral substituent with the deuterated counterparts as exemplified from the FTIR spectra has been suggested for the first time to result from the afinity of the latter compounds towards hydroxylation induced by potassium bromide.